PENGARUH PENGGUNAAN PAYLATER DAN FEAR OF MISSING OUT (FOMO) TERHADAP IMPULSE BUYING PADA GENERASI Z PENGGUNA TIKTOK SHOP DI KOTA SEMARANG - Nabila Salma Dilara; Anan Subhan Khoir; M. Rifki Bakhtiar (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of paylater usage and Fear of Missing Out (FOMO) on impulse buying among Generation Z users of TikTok Shop in Semarang. This research applied a quantitative approach involving 120 respondents selected through purposive sampling based on predetermined criteria. Data were collected using an online questionnaire with a Likert scale and analyzed using multiple linear regression with IBM SPSS Statistics. The results indicate that paylater usage has a positive and significant partial effect on impulse buying behavior. Similarly, FOMO also has a positive and significant effect, with a more dominant influence compared to paylater usage. Simultaneously, both variables have a positive and significantly affect impulse buying and contribute 35.3% to the variation in impulse buying behavior. These findings highlight the importance of improving digital financial literacy among Generation Z to reduce consumptive behavior driven by the convenience of paylater services and psychosocial pressure caused by FOMO in social commerce.